Menilik Ulang Penegakan Hukum Terhadap Pelaku Revenge Porn: Antara Efektifitas Dan Reformasi Hukum - Fitri Maryani; Jamaludin Umam (Jurnal Hukum Lex Generalis, 2025)
As a result of the rapid advancement of technology, it has a logical impact on the emergence of a crime in a new dimension, such as revenge porn. In relation to revenge porn, there are no explicit rules governing revenge porn in Indonesia, which creates obstacles and challenges in law enforcement against the perpetrators. This research aims to review the effectiveness of law enforcement and regulatory reform regarding the crime of revenge porn. The methodology used in this research is a library study in a qualitative research approach. The results of this study concluded that in law enforcement in Indonesia against the perpetrators of revenge porn crimes still use general arrangements, thus facing various challenges and obstacles that are considered less efficient. In connection with this, legal reform is needed, especially those that regulate explicitly against revenge porn crimes.